Simulation of the Corrosion Point and Repairing Technique at the Crane with Finite Element Analysis - M. M., Noor; A., Sulaiman; K., Kadirgama; M. R. M., Rejab; M. S. M., Sani; F. R. M., Romlay; R., Daud; Z., Ghazalli; D., Ramasamy; M. F., Ghazali; W. S., Wan Harun; M. Y., Taib (2008)
This paper describes the stress analysis for the corrosion area at the hollow pipe crane structure. This crane is used for lifting the load. Finite element analysis was used to, investigate the stress concentration at the corrosion point. Three stages had been simulated; first stage simulates the structure without corrosion, second stage simulates the main chord with corrosion and third stage simulates the corrosion point with patch method and clamp shell repair method. The results show that the stress concentrations at the corrosion points were double from the normal point. Clamp shell method reduces the stresses by 28.6%. This technique saves the costs and time to repair the corrosion areas.